Migration, Remittances, and Agricultural Productivity in China - Rozelle, Scott; Taylor, J. Edward; deBrauw, Alan (American Economic Review, 1999)
In our paper we have used the New Economics of Labor Migration framework to trace the complex linkages that exist among migration remittances and agricultural productivity [in China]. Constraints in the operation of on-farm labor and capital or insurance markets (or institutions) provide households with a motivation to migrate and distort on-farm operations when labor leaves. In our household sample the net impact of migration and remittances on maize production is negative. (EXCERPT)